Serum Vitamin A and Inflammatory Markers in Individuals with and without Chronic Obstructive Pulmonary Disease - Caram, L. M. O. (Mediators Inflamm, 2015)
Background. Vitamin A is essential for the preservation and integrity of the lung epithelium and exerts anti-inflammatory effects. Objective. Evaluating vitamin A in the serum and sputum and testing its correlation with inflammatory markers in individuals with or without COPD. Methods. We evaluated dietary intake, serum and sputum vitamin A, tumor necrosis factor alpha, interleukin- (IL-) 6, IL-8, and C-reactive protein in 50 COPD patients (age = 64.0 ± 8.8 y; FEV(1) (forced expiratory volume in the first second) (%) = 49.8 ± 16.8) and 50 controls (age = 48.5 ± 7.4 y; FEV(1) (%) = 110.0 ± 15.7). Results. COPD exhibited lower serum vitamin A (1.8 (1.2–2.1) versus 2.1 (1.8–2.4) μmol/L, P < 0.001) and lower vitamin A intake (636.9 (339.6–1349.6) versus 918.0 (592.1–1654.6) RAE, P = 0.05) when compared with controls. Sputum concentration of vitamin A was not different between groups. Sputum vitamin A and neutrophils were negatively correlated (R (2) = −0.26; P = 0.03). Smoking (0.197, P = 0.042) exhibited positive association with serum vitamin A. COPD was associated with lower serum concentrations of vitamin A without relationship with the systemic inflammation. Conclusions. Serum concentration of vitamin A is negatively associated with the presence of COPD and positively associated with smoking status. Sputum retinol is quantifiable and is negatively influenced by neutrophils. Although COPD patients exhibited increased inflammation it was not associated with serum retinol.